A Case Study on Teaching HCI to Interactive Art Practitioners (and Learning from Them) - Rodríguez, Andrés (2024)
The fields of HCI and interactive art have long maintained an increasingly fruitful relationship of dialogue, exchange, cross-pollination, and complementation. From an art perspective, HCI knowledge and strategies deliver novel tools for offering experiences to the public and open new possibilities for artists to investigate and experiment. From the HCI perspective, artists contribute new representations and experimentations of forms of interaction, as well as bring closer the crossover of knowledge areas that are often far from the HCI radar. This paper reports on an exploratory experience of teaching HCI concepts to interactive arts practitioners. Toe experience sought to promote a vibrant connection between both realms. We seek to understand the potential mutual influences between Interactive Art and HCI. We aim to identify the aspects of HCI that can benefit the artist's work and, in that process, recognize the insights that can be captured for the HCI agenda.